The Effect of Film on Listening Comprehension of the XI Grade Students - Rifa'i, Moh.; Nur Tjendani, Endah; Sabartono, Ribut (Linguapedia, 2022)
This study aimed to research an experimental research in teaching English listening material using English film for the Eleventh grade students of SMK Full Day Bustanul Ulum, The design English Teaching Material to improve the listening skill’s students in SMK Full Day Bustanul Ulum. The research in this study is designing English teaching material using English film to increase students’ listening skill. In this context of the research the researcher designed the listening material in the vocational high school especially in SMK Full Day Bustanul Ulum by focused on quantitative data of Experimental reseach. The data in this research were taken with a round of the object study. The steps of the study are pre and posttests, plan, implementation and questionnaires. The data were analyzed as the teaching materials for designing listening teaching materials that relevant with the vocational school. And then, the syllabus was designed based on the curriculum 2013.